2017
DOI: 10.1021/acs.orglett.7b00642
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of (+)-Lophirone H and Its Pentamethyl Ether Utilizing an Oxonium–Prins Cyclization

Abstract: The first total synthesis of (+)-lophirone H (1) and its pentamethyl ether 29, featuring an oxonium-Prins cyclization/benzylic cation trapping reaction, is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Indeed, the prevalence of 5,6- cis -fused systems in bioactive natural products ( e.g. flavonoids: lophirone H18 and cordigol;19 and pterocarpan isoflavonoids: medicarpin20 and phaseolin21) suggests their relative thermodynamic stability. Irrespective of the thermodynamic basis of the phenomenon, a reversible isomerization process renders Singleton analysis unsuitable for interrogation of the mechanism of this reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the prevalence of 5,6- cis -fused systems in bioactive natural products ( e.g. flavonoids: lophirone H18 and cordigol;19 and pterocarpan isoflavonoids: medicarpin20 and phaseolin21) suggests their relative thermodynamic stability. Irrespective of the thermodynamic basis of the phenomenon, a reversible isomerization process renders Singleton analysis unsuitable for interrogation of the mechanism of this reaction.…”
Section: Resultsmentioning
confidence: 99%
“…24 The cis ring-fusion obtained by using this protocol contrasts with the trans ring fusion obtained by the Zhao group 18 and the List group 19 for related reactions promoted by Brønsted acid catalysts (see Scheme 6). Only the cis stereochemistry is found in known natural products (e.g., flavonoids: lophirone H 26 and cordigol; 27 and pterocarpan isoflavonoids: medicarpin 28 and phaseolin 29 ), and in 2017 we reported the use of the SnCl 4 -mediated reaction as a key step in the synthesis of the pentaphenolic Lophira lanceolate extract, lophirone H. 25 DFT calculations suggested that the oxonium Prins pathway was lower in energy than the…”
Section: Stepwise Addition Reactionsmentioning
confidence: 95%
“…In 2013 the Gharpure group also utilized an oQM HDA cycloaddition reaction in their studies towards the formal synthesis of (±)-myristinin B/C (Scheme 12). 42 Scheme 10 Synthesis of furanochromane and the natural product lophirone H via a SnCl 4 -mediated oxonium Prins-type reaction 24,25…”
Section: Applications In Total Synthesismentioning
confidence: 99%
“…From a plethora available stereoselective methods for synthesizing tetrasubstituted tetrahydrofuran derivatives we planned to use Johnson's synthesis of virgatusin as the blueprint to construct the 2,5‐diaryl‐3,4‐disubstituted tetrahydrofuran scaffold.…”
Section: Figurementioning
confidence: 99%